Pengaruh inovasi pengguna dan dukungan pemerintah terhadap niat UMKM mengadopsi teknologi keuangan - Theodorus Alvin; Agus Zainul Arifin (Universitas Tarumanagara, 2023)
MSMEs (Micro, Small and Medium Enterprises) have become an important part of the economy in developing countries. However, MSMEs are often constrained in obtaining funding, especially from banking institutions. This problem can be overcome by using financial services technology, namely Peer to Peer Lending. Even though the existence of peer-to-peer lending can overcome this problem, many MSMEs do not want to use it. The purpose of this study is to find out whether the level of user innovation and government support influence MSME in using peer to peer lending. This research is descriptive research with quantitative methods. The sampling method uses purposive sampling by distributing questionnaires to 174 MSME in Jabodetabek. Data were analyzed using SEM PLS. The results of the study show that user innovation and Government Support have a positive and significant effect on the intention to use peer to peer lending. For this reason, user innovation and Government Support are considered to be able to increase the intention of MSME actors to use Peer to Peer Lending. UMKM (Usaha Mikro Kecil dan Menengah) telah menjadi bagian penting dalam roda ekonomi di Negara yang masih berkembang. Namun, UMKM sering terkendala dalam mendapatkan pendanaan terutama dari lembaga perbankan. Masalah ini dapat diatasi dengan penggunaan teknologi jasa keuangan yaitu Peer To Peer Lending. Walaupun keberadaan peer to peer lending dapat mengatasi permasalahan ini, banyak pelaku UMKM tidak mau menggunakannya. Tujuan dari penelitian ini yaitu mengetahui apakah tingkat inovasi pengguna dan dukungan pemerintah mempengaruhi niat pelaku UMKM dalam menggunakan peer to peer lending. Penelitian ini merupakan penelitian deskriptif dengan metode kuantitatif. Metode sampling menggunakan purposive sampling dengan menyebarkan kuesioner ke 174 pelaku UMKM di Jabodetabek. Data dianalisa menggunakan SEM PLS. Hasil penelitian menunjukan bahwa inovasi pengguna dan dukungan pemerintah berpengaruh positif dan signifikan terhadap intensi penggunaan peer to peer lending. Untuk itu, inovasi pengguna dan dukungan pemerintah dinilai dapat meningkatkan intensi pelaku UMKM dalam menggunakan Peer To Peer Lending.